Land Suitability for Developing Soybean Crops in Bumi Nabung and Rumbia Districts, Central Lampung - . Sudaryono; . Prihastuti; Andy Wijanarko (UNIVERSITY OF LAMPUNG, 2011)
Bumi Nabung district consists of 6 villages with a total area of 7,810 ha which are divided into 251 ha of rain fed rice lands, 4,908 ha of dry land, 1,317 ha of lowland, 1,158 ha of yards and 176 ha of others. Rumbia district consists of 14 villages which has a total area of 22,696 ha of land consisting of 2,728 ha of yards, 17,358 ha of dry land, 326 rainfed paddy field, 839 ha of swamp land, 1,470 ha of lowland and 4,232 ha of others. Bumi Nabung and Rumbia districts have a low soil fertility potential that is reflected by the lowof soil pH, CEC, total N, available P, and high level of exchangeable Al and Al saturation. The results assessment based on the physical and chemical characteristics showed that Bumi Nabung district have 5 villages on suitable class S-2 (North Bumi Nabung, East Bumi Nabung, Bumi Nabung Ilir, South Bumi Nabung, and Sri Kencono) and one village New Bumi Nabung has less suitable class S-3. In the Rumbia District, there were 14 villages belonged to suitable class (S-2), namely Reno Basuki, Rekso Binangun, Teluk Dalam Ilir, Rukti Basuki, Restu Baru, Restu Buana, Bina Karya Buana, Bina Karya Putra, Bina Karya Jaya, Bina Karya Utama, Bina Karya Sakti, Joharan, Rantau Jaya Ilir and Rantau Jaya Baru. Bumi Nabung and Rumbia districts have the potential fertility and land suitability for extensification and development of soybean crops. The main technology components to support this program are the use of ameliorant (dolomite and zeolite), the application of organic fertilizers (manure and compost) and inorganic fertilizers (NPK).Keywords: Acid soil, central Lampung, land suitability, soil fertility, soybeans